Website design as an promotional media for the brand ismage studio - Muhammad Akrif Saputra; Dian Syafitri; Hasbullah Hasbullah; Muhammad Fathoni; Ni Putu Sinta Dewi (Indonesia Accounting Research Journal, 2025)
The website serves as a vital medium for delivering information effectively and attractively, especially for businesses engaged in photography and videography, such as Ismage Studio. This thesis discusses the design of an aesthetic website as an information hub for Ismage Studio by applying an optimized UX/UI design approach. The objective of this research is to develop a digital platform that not only functions as a promotional tool but also facilitates potential clients in accessing service information and making reservations efficiently. The research methods include observation, interviews, and user needs analysis to obtain accurate data regarding customer preferences and expectations. The website design process follows UX/UI design stages, ranging from concept planning, wireframing, to visual implementation, all oriented toward an intuitive user experience. Furthermore, a well-structured service booking form is implemented to enhance customer service effectiveness. The results indicate that an aesthetic and user-friendly website design significantly enhances user engagement and information accessibility. Through this website, Ismage Studio is able to build a professional image while providing a more practical and efficient service booking experience.